2016
DOI: 10.1016/j.trpro.2016.05.492
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of the ASEAN air Transport Market: Measure of Impacts of Airport Activities on Local Economies

Abstract: International audienceASEAN Member States are currently in a step through liberalization of air traffic market in their region. The target is the 5th freedom right for South-East Asia in 2020. Two opposite effects might be observed following the deregulation: one negative on flag carrier due to increase in competition, one positive on national and regional economies. One main issue concerns the impact of expected development of airport activity on national and regional economies. We propose an estimation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
1
2
0
1
Order By: Relevance
“…Some previous studies also suggested that growth in GDP was very sensible to growth in air traffic for time dimension [13,14], findings from this study further indicate that air transportation is strongly associated with GDP across cities in China. Indeed, results from this study identified that only the intercity air transportation (in terms of both air passenger traffic and freight volume) have noticeable influence on GDP at the national level and in all the three regions.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Some previous studies also suggested that growth in GDP was very sensible to growth in air traffic for time dimension [13,14], findings from this study further indicate that air transportation is strongly associated with GDP across cities in China. Indeed, results from this study identified that only the intercity air transportation (in terms of both air passenger traffic and freight volume) have noticeable influence on GDP at the national level and in all the three regions.…”
Section: Discussionsupporting
confidence: 80%
“…Laplace and Latgé-Roucolle [14] examined the relationship between the economic development and the air traffic in four ASEAN countries including Lao PDR, Myanmar, the Philippines and Vietnam. Their findings pointed out that GDP was very sensible to air traffic growth, especially in the regions which owns only one international airport.…”
Section: Introductionmentioning
confidence: 99%
“…Keanekaragaman ini dimunculkan eksotisme alam sehingga dapat dijadikan obyek wisata. TINJAUAN PUSTAKA Laplace and La (2016) menyebutkan negara-negara Anggota ASEAN saat ini dalam langkah liberalisasi pasar lalu lintas udara di wilayah mereka. Sasarannya adalah hak kebebasan lalu lintas untuk Asia Tenggara pada tahun 2020.…”
Section: Pendahuluanunclassified
“…The capacity of an airport depends on the capacities of its landside and airside components in accommodating passenger movements, cargo and aircraft takeoff, and airport landing movements [3]. Based on Laplacea, et al (2016), the population growth, GDP, and the fluctuation of the per capita incomes in a specific region may affect airport traffic movements [4].…”
Section: Introductionmentioning
confidence: 99%